Structural and electrical effects of Ag substitution in tungsten bronze Sr2AgxNa1−xNb5O15 ceramics. Issue 9 (15th June 2020) - Xu, Shudong; Deng, Zhuo; Shen, Saijiao; Wei, Lingling; Yang, Zupei
Abstract: In this work, the correlation between the composition and structure of the Sr2 Ag x Na1− x Nb5 O15 (SANN, 0.00 ≤ x ≤ 1.00) ferroelectric ceramic was investigated. The SANN ceramic was synthesized via the solid-state reaction method and equivalently charged Ag + cations were doped in the SANN matrix to investigate the relationship between the composition and structure. Investigation of the ceramic's properties mainly focused on two aspects: (1) enhancement of the dielectric and ferroelectric properties caused by the dense structure, increased orthorhombic distortion, and increased disorder distribution; (2) the low-temperature dielectric anomaly evolved from a slightly smeared out phase transition into an obvious ferroelastic/ferroelectric phase transition by Ag + introduction in SANN. In addition, improved light transmittance was realized at x = 1.00, which may be related to the homogeneous equiaxed microstructure and uniform size of the ceramic grains.